Fibrin Scaffold Incorporating Platelet Lysate Enhance Follicle Survival and Angiogenesis in Cryopreserved Preantral Follicle Transplantation: - Talebi, Ali; Rajabzadeh, Alireza; Jahanpeyma, Fatemeh; Moradi, Faezeh; Eimani, Hussein; Hamidieh, Amir Ali (Galen Medical Journal, 2020)
Background: Transplantation of cryopreserved follicles can be regarded as a promising strategy for preserving fertility in cancer patients under chemotherapy and radiotherapy by reducing the risk of cancer recurrence. The present study aimed to evaluate whether fibrin hydrogel supplemented with platelet lysate (PL) could be applied to enhance follicular survival, growth, and angiogenesis in cryopreserved preantral follicle grafts. Materials and Methods: Preantral follicles were extracted from 15 four-week-old NMRI mice, cryopreserved by cryotop method, and encapsulated in fibrin-platelet lysate for subsequent heterotopic (subcutaneous) auto-transplantation into the neck. Transplants were assessed in three groups including fresh follicles in fibrin-15%PL, cryopreserved follicles in fibrin-15%PL, and cryopreserved follicles in fibrin-0% PL. Two weeks after transplantation, histological, and immunohistochemistry (CD31) analysis were applied to evaluate follicle morphology, survival rate, and vascular formation, respectively. Results: Based on the results, fibrin-15% PL significantly increased neovascularization and survival rate (SR) both in cryopreserved (SR=66.96%) and fresh follicle (SR=90.8%) grafts, compared to PL-less fibrin cryopreserved transplants (SR=28.46%). The grafts supplemented with PL included a significantly higher percentage of preantral and antral follicles. Also, no significant difference was observed in the percentage of preantral follicles between cryopreserved and fresh grafts of fibrin-15% PL. However, a significantly lower (P=0.03) percentage of follicles (23.37%) increased to the antral stage in cryopreserved grafts of fibrin-15%PL, compared to fresh grafts (35.01%). Conclusion: The findings demonstrated that fibrin-PL matrix could be a promising strategy to improve cryopreserved follicle transplantation and preserve fertility in cancer patients at the risk of ovarian failure. [GMJ.2020;9:e1558]